A Conceptual Model for Iranian Older Women's Health: A Review Study - Kamran Shahanaghi; Seyed Mojtaba Hosseini; Soodabeh Tayeri; Khalil Alimohammadzadeh; Mehrnoosh Jafari (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Studies have indicated the feminization of aging in the world including Iran. The present study aims to investigate women's aging trend and effects, status difference, factors affecting the health of older women, and how to achieve proper health for older women in Iran. Methods & Materials: This review study was conducted according to PRISMA checklist. A comprehensive search was conducted in online databases including PubMed, Scopus, Elsevier, IranMedex, IranDoc, MagIran, NoorMags, SID, Google Scholar, and websites of the World Health Organization and the United Nations Population Fund on articles published until June 2020 using the keywords Elderly, Aged, Healthy Aging, Older Women and Health Services in English and Persian. Results: Increased population of older women and the feminization of aging is the result of the development and success of the health system. Poor aging management is a serious threat to health care, socio-economic and sustainable development systems. The differences in economic, social, demographic, and health indicators were more unfavorable in older women compared to older men due to different effects of health factors on women. The geriatric programs in Iran are often temporary without participation of the elderly, and are for managing individual, clinical, and case conditions. Provision of integrated care services is only at the first level of health and government services and lacks strategic, gender, and inter-sectoral approaches. Conclusion: Achieving older women's health requires policy-making and planning at the levels of government, organization and service delivery with a gender justice approach. Interventions to achieve the goal should be elderly-centered, interactive, multi-disciplinary, continuous, participatory, coordinative at clinical, organizational and systemic levels with analysis, feedback, integrated information system, research and development. Training and employment of multi-skilled manpower considering the different needs of older women are recommended.